Comparative Analysis of Approaches to Geothermal Resource Risk Mitigation : A Global Survey - World Bank Group (World Bank, Washington, DC, 2016)
Based on the World Bank’s own extensive global experience and drawing upon international expertise from leading specialists and practitioners, this report presents a comparative assessment of various approaches that have been applied around the world, with varying degrees of success, to mitigate resource risks and catalyze investments in developing the geothermal sector. It provides a framework that can help decision makers identify suitable approaches that are commensurate with development goals, funding capacity, implementation capabilities, and other circumstances specific to the context in a given country. Geothermal presents an opportunity for many countries to diversify their power generation mix in a sustainable way since it is an environmentally friendly, clean energy source that can reliably produce baseload power on a 24 by 7 basis. Despite over 100 years of development and an estimated global potential of 70 - 80 gigawatts (GW), only about 15 percent of the known geothermal reserves are presently exploited and producing electricity. While there are many reasons, in various countries, for the slow pace of geothermal development, one widely recognized and unique obstacle that is applicable worldwide is the high resource risk during the early stages of the geothermal development process. As a result, it is difficult to mobilize the early-stage investments, especially through the private sector.